Оросын Ерөнхийлөгч Владимир Путины олон тулгуурт гадаад бодлогын тухай - Д, Эрдэнэ-Отгон (Journal of International Studies, 2003)
English title: Multi-pillared foreign policy of Russian Federation's President Vladimir Putin